Дослідження можливості використання алгоритму Прюіт для обробки медичних зображень - Дерюга, І. М.; Чумак, В. С. (ХНУРЕ, 2023)
In the context of rapid advancements in medical technologies and the increasing utilization of digital technologies in the healthcare sector, addressing challenges in medical image processing becomes crucial. Computational methods for analyzing boundaries in images obtained from various scanning devices have garnered particular interest. This article explores the application of the Pruitt algorithm for detecting boundaries in medical images. The use of FPGA is proposed for implementing this algorithm to optimize productivity and real-time image processing speed. Experimental results underscore the importance of further research and refinement of medical image processing algorithms to achieve improved accuracy and efficiency in diagnostics.
Keywords: алгоритм Прюіт; FPGA; обробка медичних зображень